Intersection of different disciplines: Elements - ŞAHİN, FATMA (ELSEVIER SCIENCE BV, 2010)
This study aims to reveal the extent to which 7th grade students are able to integrate the use of elements topic into different disciplines, to determine their way of accomplishing this integration. The study is conducted with 37 seventh grade students in a private school in Istanbul in 2008-2009. Integration of Elements Test (IET) is administered both as a pretest and a posttest and activity sheets are formed to be used during the treatment. After the completion of the treatment, a semi-structured interview is conducted with 4 randomly selected students and they are videotaped and analyzed qualitatively. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Interdisciplinary learning; science education; science learning; elements; elementary education